The innovative structure of physical education lessons for students in romanian educational institutions (late XIX - early XXI Century) - Цибанюк; Tsybanyuk, Олександра; Oleksandra; Gnes, Гнесь, Nataliia, Наталия; Strazhnikova, Inna; Дарійчук, Сергій (Revista Eduweb, 2023)
The research aims to establish the regularity of promoting the implementation of the innovative structure of PE lessons for students in Romanian educational institutions (late XIX - early XXI century). As a result of the study, it was found that students of educational institutions noted that coordination exercises (98.3%), game and competitive exercises (95.5%), breathing exercises (94.1%), rhythmic exercises (93.8%), exercises in various and imitation walking (92.4%), etc. have a positive impact on the development of physical culture in students. It was found that teachers most often use the following game exercises in the innovative structure of physical education lessons: "One and Two" (95.6%), "Do this, ¡do that!" (95.5%), "Crabs and Shrimps" (89.7%), "Train" (89.6%), "Chapel Hijack" (89.2%), "Boat" (89%), etc. It has been found that teachers use cooperative group learning (89.7%),interactive methodological and organizational complex (89.2%), and multimedia technologies (89%) in PE lessons.
Keywords: innovative lesson structure, physical education, students, educational institutions, Romania